Assessment of the Low-Cycle Strain-Induced Martensite Transformation in AISI 316 Stainless Steel by Magnetic and Acoustic Nondestructive Methods - Kim, C.S. (Проблемы прочности, 2018)
The strain-induced martensite transformation during the low-cycle fatigue in austenitic AISI 316 stainless steel was investigated by magnetic and acoustic nondestructive methods. The low-cycle fatigue test was performed at various strain amplitudes. The volume fraction of α’-martensite was determined for the fatigue-failed specimens by magnetic property measurements with further microstructure detection. The cyclic hardening behavior was discussed in terms of the α’-martensite transformation. The volume fraction of α’-martensite was growing with the strain amplitude. An increase in the α’-martensite fraction was evaluated with the nonlinear ultrasonic parameter. The α’-martensite fraction may distort the lattice in austenitic stainless steel, resulting in the distortion of an ultrasonic wave. From this distortion, superharmonics may be generated with the α’-martensite nucleation, which strongly depends on the strain amplitude. The relationship between nonlinear acoustic characteristic and the volume fraction of α’-martensite is linear.